Effective Building Surveying Using Laser Scanning for Heritage Building Documentation - Said, Shahrul Yani; Shahrin, Muhammad Shahir; Johari, Muhammad Naqiuddin; Abdullah, Ahmad Sharim; Harun, Siti Norlizaiha; Abd Latif, Zulkiflee; Salleh, Nurul Hamiruddin; Wongso, Jonny (International Journal of Sustainable Construction Engineering and Technology, 2023)
In conservation works, a thorough pathology survey is required to identify building defects. Early detection of defects can prevent the increase in cost during conservation works. Conventionally, common defects that occur in heritage buildings can be observed and recorded during a walk-by inspection; however, the process is often time consuming. Furthermore, all recorded defects require a precise but conventional data collection to identify, test, and observe the level of defects. This study aims to compare the effectiveness of manual walk-in building condition assessment with the point cloud data analysis that utilises the Light Detection and Ranging (LiDAR) technology. A building condition assessment was conducted involving the Ipoh Town Hall and Post Office, Galeri Kraftangan Seremban, and Bangunan Dato’ Jaafar in Johor Bahru using both conventional walk-in survey and the laser scanning process. This study concludes that combining digital tools with the traditional methods promotes a more accurate and effective assessment for heritage building assessment, which is crucial for ensuring the sustainability of historic structures. Additionally, 3D point cloud data allows the exploration of building deterioration from a wider perspective.